NEWMAN’S ERROR ANALYSYS DALAM PENYELESAIAN SOAL MATEMATIKA PADA PESERTA DIDIK KELAS VIII SMP PEMBANGUNAN PADANG - Suhardi, Okdri Putri (Jurnal Edukasi dan Penelitian Matematika, 2023)
The assessment results provide a means of observing the learning outcomes in mathematics. The study's findings indicate that the academic achievements of eighth-grade pupils at Padang Development Junior High School remain subpar. This phenomenon arises due to errors committed throughout the process of problem-solving. Consequently, a comprehensive examination of these errors is conducted in order to identify the mistakes made by pupils, utilizing Newman's Error study as the basis for study. The present study used a descriptive research design. The participants in this study consisted of pupils enrolled in the eighth grade.The SMP Pembangunan Padang is a secondary school located in the city of Padang. The data analysis reveals the presence of many sorts of errors, including reading and comprehension errors, transformation errors, process skills faults, and final response writing errors. Keywords– Mathematics Problem, Newman’s Error Analysis, Student of SMP Pembangunan Padang